PENTINGNYA DEREGULASI TERHADAP NEOLIBERALISME SISTEM PENDIDIKAN TINGGI DI INDONESIA - Riyanti, Ratna; Miswar, Miswar (Jurnal Pahlawan, 2024)
Deregulation in the higher education system in Indonesia plays a significant role in strengthening neoliberalism, which emphasizes privatization, efficiency, and competition. This policy aims to increase institutional autonomy, but also raises challenges such as the commercialization of education and inequality of access. This study analyzes the impact of deregulation on the quality of education, the welfare of academics, and opportunities for students from various social strata. With a critical approach, this study evaluates the extent to which deregulation can increase global competitiveness without sacrificing the principle of social justice in higher education. The results are expected to provide policy recommendations that balance economic efficiency and educational accessibility. Keywords: Deregulation, Neoliberalism, Higher Education System